Exploring Cultural Factors of Human Papillomavirus Vaccination Acceptance in African Americans: An Integrative Review. (November 2022) - Henderson, Rashida L.; Zoucha, Rick; Colbert, Alison; Braxter, Betty J.
Introduction: Human papillomavirus (HPV) vaccine can prevent HPV-related cancers. However, African Americans (AA) have a 30% higher incidence of HPV-related cervical cancer than Whites. The purpose of this integrative review is to explore cultural factors and beliefs impacting HPV vaccine decisions in AA adults. Methodology: The Whittemore & Knafl model guided this review. Databases searched were PubMed, CINAHL, and Embase. Key terms included "human papillomavirus, " "vaccine, " "cultural values, " "African American, " and "adult." Inclusion criteria were AAs aged 18 years and over living in the United States. Results: A total of 634 articles were identified, and 20 studies published from 2010 to 2020 were used. Common factors influencing HPV vaccine decisions included religion, knowledge, physician recommendation, social network, attitudes, mistrust, benefits, and safety. Discussion: Limitations included omission of articles lacking AA representation, limited databases searched, and one-author-evaluated studies. Future studies to discover additional cultural factors influencing HPV vaccine acceptance are critical.